2008
DOI: 10.1124/dmd.107.019000
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pharmacokinetic Drug-Drug Interactions Using Human Hepatocyte Suspension in Plasma and Cytochrome P450 Phenotypic Data. III. In Vitro-in Vivo Correlation with Fluconazole

Abstract: ABSTRACT:Whereas ketoconazole is often used to study the worst-case scenario for clinical pharmacokinetic drug-drug interactions (DDIs) for drugs that are primarily metabolized by CYP3A4, fluconazole is considered to be a moderate inhibitor of CYP3A4, providing assessment of the moderate-case scenario of CYP3A-based DDIs. Fluconazole is also a moderate inhibitor of CYP2C9 and CYP2C19. For predicting clinical DDIs using conventional approaches, determining the in vivo inhibitor concentration at the enzymatic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…Prediction of drug-drug interactions using in vitro data has been extensively explored using both static and dynamic models, and considerable success has been achieved (Ito et al, 2005;Obach et al, 2006;Lu et al, 2008;Fahmi et al, 2008;Rowland Yeo et al, 2010). For intravenously administered drugs, it has been suggested that this type of modeling can be used for prediction assuming a very low hepatic EH (Kirby and Unadkat, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prediction of drug-drug interactions using in vitro data has been extensively explored using both static and dynamic models, and considerable success has been achieved (Ito et al, 2005;Obach et al, 2006;Lu et al, 2008;Fahmi et al, 2008;Rowland Yeo et al, 2010). For intravenously administered drugs, it has been suggested that this type of modeling can be used for prediction assuming a very low hepatic EH (Kirby and Unadkat, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…NA, data not available (compounds are not time-dependent inhibitor of CYP3A4 based on data in Table 3). a A static model described by Kirby and Unadkat (2010) was used by incorporating parallel pathways (Ito et al, 2005;Lu et al, 2008) and with the consideration of EH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our in vitro assays, we used human hepatocytes suspended in human plasma, with the plasma concentration of the inhibitors in the incubations being similar to the clinical C max of the inhibitor observed with standard dosing. The free concentration at the enzyme site would be same in the two systems (Lu et al, 2007(Lu et al, , 2008a. Consequently, our model eliminates the need to determine the value of [I] and removes the dependence on the traditional, less desirable rule of [I]/K i ratio to predict magnitude of DDIs.…”
mentioning
confidence: 99%